1999
DOI: 10.1074/jbc.274.10.6161
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-lysine)-graft-dextran Copolymer Promotes Pyrimidine Motif Triplex DNA Formation at Physiological pH

Abstract: Extreme instability of pyrimidine motif triplex DNA at physiological pH severely limits its use for artificial control of gene expression in vivo. Stabilization of the pyrimidine motif triplex at physiological pH is therefore of great importance in improving its therapeutic potential. To this end, isothermal titration calorimetry interaction analysis system and electrophoretic mobility shift assay have been used to explore the thermodynamic and kinetic effects of our previously reported triplex stabilizer, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 42 publications
9
73
0
Order By: Relevance
“…The length of the single-stranded oligo was chosen such as to avoid loop formation with a single siRNA molecule. However, formation of nucleic acid networks bridged by antiparallel T⅐A helices and antiparallel/parallel T⅐A⅐T triple helices (26) are possible in the presence of a polycation. Other experiments showed that using either oligoribo or oligodeoxyribo sequences as added single-stranded oligonucleotides led to significant enhancement of silencing (data not shown).…”
Section: Ssirna-mediated Silencing Is Specific and Does Not Trigger Amentioning
confidence: 99%
“…The length of the single-stranded oligo was chosen such as to avoid loop formation with a single siRNA molecule. However, formation of nucleic acid networks bridged by antiparallel T⅐A helices and antiparallel/parallel T⅐A⅐T triple helices (26) are possible in the presence of a polycation. Other experiments showed that using either oligoribo or oligodeoxyribo sequences as added single-stranded oligonucleotides led to significant enhancement of silencing (data not shown).…”
Section: Ssirna-mediated Silencing Is Specific and Does Not Trigger Amentioning
confidence: 99%
“…EMSA experiments for the triplex formation were performed essentially as described previously by a 15% native polyacrylamide gel electrophoresis [12,13,[19][20][21][22][23][24][25][26][27]. In a 9 µl of reaction mixture, 32 P-labeled Pur23A•Pyr23T duplex (~1 nM) (Figure 1c) was mixed with increasing concentrations of the specific TFO (Pyr15TM, Pyr15NC7-1, Pyr15NC7-2, Pyr15NC5-1, or Pyr15NC5-2) (Figure 1c) and the nonspecific oligonucleotide (Pyr15NS2M) (Figure 1c) in buffer [50 mM Tris-acetate (pH 7.0), 100 mM NaCl, and 10 mM MgCl2].…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
“…Isothermal titration experiments for the triplex formation were carried out on a VP ITC system (Microcal Inc., U.S.A.), essentially as described previously [12,13,[19][20][21][22][25][26][27]. The TFO (Figure 1c) and Pur23A•Pyr23T duplex (Figure 1c) solutions were prepared by extensive dialysis against 10 mM sodium cacodylate-cacodylic acid at pH 6.1 or pH 6.8 containing 200 mM NaCl and 20 mM MgCl2.…”
Section: Thermodynamic Analyses By Isothermal Titration Calorimetry (mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The copolymer with a high degree of grafting forms totally soluble DNA complexes without inducing collapse. 3 We have shown that PLL-g-Dex increases stability of DNA hybrids, 2 accelerates DNA hybridization, 4 and activates DNA strand-exchange reactions. 5 However, interaction of the copolymer with DNA is not thoroughly understood and the influence of the copolymer grafting degree on conformation of DNA has not been assessed.…”
mentioning
confidence: 99%